PRESSURE LEVELS AND RISK FACTORS FOR SYSTEMIC ARTERIAL HYPERTENSION AMONG NURSES FROM A HOSPITAL IN ALTO SERTÃO PARAIBANO (Fiep Bulletin - online, 2012)
Cardiovascular diseases are common causes of morbidity and mortality all over the world. Among them, arterial hypertension is responsible for about 40% of cases of precocious retirement and absenteeism at work. Objective: to investigate blood pressure and risk factors to the systemic arterial hypertension among nurses. Methods: It is an exploratory-descriptive and field study with quantitative approach, developed at Deputado Manuel Gonçalves de Abrantes District Hospital (DMGADH). Population formed by 66 nurses, and a sample of 40 ones was selected according to the inclusion criteria. A structured questionnaire was applied to analyze clinical, demographic and socioeconomic characteristics. It was based on the 6th Brazilian Guidelines for Arterial Hypertension. With this questionnaire, the Likert Scale was applied and it evaluated work activity. A descriptive analysis of data was done with the SPSS® software (Version 17.0). All the terms of Resolution n. 196/96 of the National Health Council/ MH were fulfilled. Results and Discussions: the research evidenced that 80% of the interviewees were women, white, and at age group from 25 to 30 years old. In relation to blood pressure, only 2.5% of the group declared themselves as hypertensive, but when the blood pressure was measured, 17.8% presented high blood pressure. Among some risk factors, the study observed that 57.5% of the interviewees were sedentary, 40% were overweight, and 12.5% presented obesity. In relation to the opinions about the work activity, it was verified the existence of social support by interpersonal relations; exigency of a big psychological demand; presence of autonomy. However, many nurses demonstrated unsatisfied with their activities. Conclusion: Nurses have a work routine with high psychological demand, excessive workload and some risk factors – modified or unmodified, what become them inclined to the development of SAH.
Keywords: Risk factors; Hypertension; Work in nursing.